Capacidade combinatória e divergência genética entre híbridos comerciais de milho recomendados para a Região Centro-Sul do Paraná - Oliboni, Rodrigo (2009)
Twelve corn hybrids recommended for cropping in South-Central of Paraná State and the 66 crosses obtained among them were evaluated for combining ability in a complete diallel, Griffing`s method II. These genotypes and three checks were evaluated in randomized complete block design with three replications, in three experiments carried out in Laranjeiras do Sul, Guarapuava and Cantagalo-PR, Brazil. Data of days to male flowering, prolificacy, de-hulled ear yield, plant height and ear height were assessed. Also the heterosis were estimate. Data from the measuring of 22 morphological/agronomical traits of parents were submitted to a multivariate joint analysis of variance and clustered analysis for grouping parents by neighbor method, using generalized distance of Mahalanobis. In the joint diallel analysis, significant differences were observed for general combining ability (GCA) and for interactions GCA x locations for all traits. The specific combining ability (SCA) were not significant only for male flowering and interaction SCA x locations were significant for male flowering and ear height. Hybrids P30F53, P30F44, AS1575 and 2B688 were outstanding for GCA and de- hulled ear yield, in both localities, showing greater potential to generate superior inbred lines, promising for breeding purpose. The crosses P30F44 x Sprint and P30F44 x 2B688 showed high yield and high values of SCA, and also have a parent with high GCA. The cross P30F44 x 2B688 also presented the lowest values of plant height and ear height. Non-additive effects were important for male flowering, de-holled ear yield and plant height, while for prolificacy the additive effects were more important. Estimates of genetic divergence were not efficient in predicting the most heterotic crosses because Pearson`s correlation between D2 and heterosis and between D2 and CEC were not significant. Positive and significant correlations were observed between yield means and CEC and heterosis.